German Poetry in Musical Motion - Caden J. Lantz (Musical Offerings)
The musical era of Romanticism leaped forward from the individuality of Beethoven and developed composers that were unafraid of expressing their passions through their music. The leading figures of Romanticism, like Schubert and Liszt, no longer saw themselves as servants of their audiences but instead made it their goal to show what they loved in their music. Even despite the stark individualism that was prevalent in this era, there was a shared passion many composers had that was able to unify them, a love for poetry. By studying emotive vocal genres like the German Lied as well as the influences of poetic literature on purely instrumental works, poetry is revealed to be a common trait in the Romantic era.